Wazungu missionaries and Vimbuza performers: Contradictions in northern Malawi - Kamanga, Chrispine N. (Hervormde teologiese studies, 2025)
This article describes the confusion, inconsistencies, and contradictions between white people (Wazungu) and Vimbuza ritual practitioners in Malawi. It reflects on the ritual’s continuity, persistence and resistance despite the strides in Western medicine, Christianity and modernity. How can indigenous people deal with the inconsistencies and confusion brought by Wazungu in the Vimbuza ritual performance? On one hand, the missionaries displayed inconsistent and contradictory approaches to Vimbuza ritual performance. On the other hand, the local people inconsistently responded to their conversion call. From the discussions with the local people and indeed from their perception, one can note that the missionaries’ refusal of Vimbuza ritual was done out of their hatred and condemnation of African rituals. This article that indigenous people are still displaying two identities: that of being Christian and active ritual performers. Contribution: The ritual performance has been strengthened and validated further through the Wazungu’s involvement in Vimbuza ritual, a ritual that they rejected when they brought Christianity to the area.